Analysis of the inhibition of N-nitroso-dimethylamine activation in the liver by N-nitro-dimethylamine using a new non-linear statistical method - Frei, Eva; Gilberg, Frank; Schröder, Manuela; Breuer, Andrea; Edler, Lutz; Wießler, Manfred (Carcinogenesis, 1999)
N-nitro-dimethylamine (NTDMA) is carcinogenic to rats: it induces nasal cavity tumours. It can be demethylated to N-nitromethylamine and formaldehyde and reduced to N-nitroso-dimethylamine (NDMA): a potent liver carcinogen and also of the nasal cavity if activation in the liver is blocked. To explain the mechanism of NTDMA carcinogenicity we compared its demethylation with that of NDMA in liver microsomes from female and male rats, untreated, fasted or treated with ethanol to induce cytochrome P450 2E1 (CYP2E1). Kinetic parameters were analysed by non-linear statistical methods, which yielded unbiased parameter estimates for the calculated Km and Vmax values. Km for both compounds was very similar in females (24–47 μM) whereas Vmax for NTDMA was consistently higher than for NDMA as substrate: 1.07–4.70 nmol formaldehyde/mg microsomal protein × min and 0.52–2.76 nmol, respectively. In liver microsomes from induced male rats NTDMA was found to be a much more effective inhibitor of NDMA activation (KEI 39.6–73.6 μM) than NDMA of NTDMA demethylation (KEI 224–286 μM). Nasal microsomes can demethylate both NDMA and NTDMA but the kinetics are vastly different. NTDMA is demethylated at a linear rate and ~10-fold more effectively than NDMA. The mechanism of carcinogenicity of ingested NTDMA, we propose, is a partial reduction to NDMA in the liver and inhibition of NDMA activation in the liver by residual NTDMA, which enables NDMA to reach the nasal mucosa where it is activated to DNA-alkylating species and the observed tumours are formed.